Stability of Fibonacci Functional Equation (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, we solve the Fibonacci functional equation, f(x)=f(x-1)+f(x-2) and discuss its generalized Hyers-Ulam-Rassias stability in Banach spaces and stability in Fuzzy normed space.